AN ANALYSIS OF THE ABILITY OF EFL STUDENTS TO TRANSLATE OPINION ARTICLES FROM AN ENGLISH-LANGUAGE DIGITAL NEWSPAPER - Andriani, Hafizah; Risnawati; Haryanto, Endang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study investigates the ability of EFL students in translating opinion articles from English-language digital newspapers and identifies the translation strategies they employ. Translating opinion texts is considered challenging due to the use of persuasive language, idiomatic expressions, and cultural nuances, which require both linguistic competence and strategic decision-making.This research employed a descriptive quantitative design involving 30 students of the English Education Study Program at Universitas Islam Negeri Fatmawati Sukarno Bengkulu who had completed at least one translation course. Data were collected through a translation test using an opinion article from The Jakarta Post and a questionnaire based on Baker’s (1992) taxonomy of translation strategies. The students’ translations were evaluated using Nababan’s (2012) Translation Quality Assessment, focusing on accuracy, acceptability, and readability. The results show that students’ overall translation ability is at a moderate level, with an average score of 59.63. Most students are categorized as fair (50%), followed by good (37%), poor (10%), and excellent (3%). Among the assessment aspects, accuracy is the most problematic, while acceptability and readability are relatively better. The findings indicate that although students can produce natural and understandable translations, they still face difficulties in conveying meaning accurately, especially in handling abstract ideas and complex arguments. In terms of strategies, students tend to use meaning-oriented approaches, particularly paraphrasing, followed by generalization and loan words.In conclusion, students demonstrate moderate translation competence but need improvement in accuracy, deeper text comprehension, and the use of varied strategies. Keywords: EFL students, translation ability, translation strategies, opinion articles.